MEMPROGRAMKAN PENGENALAN MANAJEMEN WAKAF DI DESA CINANGKA, KECAMATAN CIAMPEA, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Mohamad Kharis Mubarok; Munandar (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
This community service aims to program the introduction of waqf management. The subject of this community service is the people of Cinangka Village, Ciampea District, Bogor Regency, West Java Province. In community service activities are carried out that provide knowledge about waqf management. With the knowledge of waqf management, the community must be able to organize existing human resources to carry out waqf management properly. With this community service, it can be concluded that people who are involved in waqf management will increase their knowledge and welfare and of course will directly add to the insight of the community. In addition, with the existence of a community that organizes its own human resources, it is hoped that it can become an extension in introducing and educating ordinary people to get involved in waqf activities that involve formal institutions in rural areas as well as regional and central government.